2010
DOI: 10.4155/bio.10.159
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Considerations as to When to Use Dried Blood Spot Sampling

Abstract: In the past few years there has been a large increase in the reporting of the use of dried blood spots (DBS) in drug development. Most of these reports pertain to the technological improvements that have allowed for drug concentration measurements from microliter volumes of sample, issues concerning method development, and exploration of the technique, into other areas such as measurement of macromolecules and metabolite identification. One area that has received less attention and is the subject of this comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(84 citation statements)
references
References 34 publications
0
83
0
Order By: Relevance
“…The concentrations of all triazoles in DBS samples were in good agreement with those in plasma. Previous studies on DBS analysis showed that the hematocrit value and the blood spot volume may influence the analysis results for DBS samples (31)(32)(33)39). For analysis of the triazoles, the hematocrit value and blood spot volume had only a minor influence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentrations of all triazoles in DBS samples were in good agreement with those in plasma. Previous studies on DBS analysis showed that the hematocrit value and the blood spot volume may influence the analysis results for DBS samples (31)(32)(33)39). For analysis of the triazoles, the hematocrit value and blood spot volume had only a minor influence.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of posaconazole in plasma were slightly higher than those in DBSs. This difference might be caused by a difference in protein binding, which is Ͼ98% for posaconazole (18), or the different distributions of the drug in whole blood and plasma, since the same difference was also observed between concentrations in VDBS and plasma samples (39). Although labeled isotopes are preferred as internal standards when mass spectrometry is used, with the use of cyanoimipramine as an internal standard, no ion suppression was observed during analysis of six lots of pooled human serum and the simultaneous direct infusion of a stock solution containing fluconazole, voriconazole, or posaconazole and cyanoimipramine (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies on DBS analysis of other drugs, several technical factors were pointed out that have to be considered when interpreting DBS analysis, such as the effect of Hct and blood spot volume (12,13,18,30). For the analysis of linezolid in DBS samples, the effect of Hct seemed to be of minor concern.…”
Section: Discussionmentioning
confidence: 99%
“…DBS specimens are commonly used for neonatal screening of metabolic diseases, cystic fibrosis and hypothyroidism in micro-blood samples. Some studies recently evaluated the use of DBS for therapeutic drug monitoring (TDM) and toxicology in adults [9,10]. Some studies, also from our group, applied the DBS technique to evaluate drug concentrations in newborns, infants and children [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%